Pendidikan Ahlak yang Terkandung Dalam “Biografi Umar Bin Khattab” Karya Ali Muhammad Ash-Shallabi (kajian pendidikan Islam) - Imas Siti Masuroh (Program Pascasarjana Institut Agama Islam Tasikmalaya, 2023)
This study used the literary method, namely the data source was obtained from literature/references related to the educational values contained in Umar bin Khattab's leadership, both in the form of books, papers, and other written sources contained in magazines. From the study of data sources, it can be concluded that Umar bin Khattab's personality and characteristics were a factor in his success in carrying out his leadership. These characteristics have implications for education, especially Islamic education. From firmness which has implications for the formation of discipline, then from an attitude of patience which has implications for perseverance, and from an attitude of sincerity which has implications for the formation of humility, then an attitude of authority has implications for wisdom, and finally, justice which is the embodiment of balance. It can be formulated that these are educational values that can be taken and made into reference material for educators and can be realized in a real way..